1996
DOI: 10.1590/s0036-46651996000200012
|View full text |Cite
|
Sign up to set email alerts
|

Human enterovirus infection in stray dogs. Some aspects of interest to public health

Abstract: To investigate the possible role of domestic animals as reservoirs of human enteroviruses, we studied 212 stray dogs captured in different areas of the municipality of São Paulo. The captured animals were divided into 19 groups of 10 to 20 dogs each; faeces of 126 of the 212 dogs were processed for enterovirus isolation. The following viruses were isolated from 12 dogs: poliovirus type 1 (2 dogs), poliovirus type 3 (1 dog), echovirus type 7 (8 dogs) and echovirus type 15 (1 dog). Of the 12 infected animals, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Human enteroviruses were detected in the faeces of dogs in Brazil with incidence between 1.5 and 11% of the dogs (Waldman et al, 1996). polio, echo and Coxsackie) can also be present in pet faeces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human enteroviruses were detected in the faeces of dogs in Brazil with incidence between 1.5 and 11% of the dogs (Waldman et al, 1996). polio, echo and Coxsackie) can also be present in pet faeces.…”
Section: Resultsmentioning
confidence: 99%
“…polio, echo and Coxsackie) can also be present in pet faeces. Human enteroviruses were detected in the faeces of dogs in Brazil with incidence between 1.5 and 11% of the dogs (Waldman et al, 1996). It was reported that enteroviruses were detected in 10% of the dog faeces that were tested at an average concentration of 5.0 Â 10 5 plaque forming units (PFU) g À1 (Clapper, 1970;Grew et al, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…The endemic and epidemic viruses vary annually and also between different areas, and are often found in sewage, surface water and seawater [11][12][13][14]. Human enteroviruses are mostly restricted to humans but several of them have occasionally been detected also in animals [15][16][17]. Along with an increased standard of living, improved hygiene and diminished crowding may have decreased the transmission rate of enteroviruses in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, although this is the first identification of EV-C99 in dogs, EV infections in dogs have been extensively investigated from the 1960s to the 1990s. These investigations sought to understand how polioviruses and enteroviruses are perpetuated for a better global eradication of polioviruses [51,52]. In these studies, detection of neutralizing antibodies in blood and viral isolation from feces or nasal swabs showed that human EVs, including coxsackieviruses, polioviruses and human echoviruses, can infect dogs.…”
Section: Enterovirusesmentioning
confidence: 99%
“…In these studies, detection of neutralizing antibodies in blood and viral isolation from feces or nasal swabs showed that human EVs, including coxsackieviruses, polioviruses and human echoviruses, can infect dogs. [51,52]. The first identification of an EV-C99 strain dates back to 2000.…”
Section: Enterovirusesmentioning
confidence: 99%